271. Digital breast tomosynthesis with photon counting technology: Dosimetric data from a preliminary clinical comparison study. (December 2018) - del Vecchio, A.; Loria, A.; Venturini, E.; Panizza, P.; Signorotto, P.
Abstract : Purpose: The aim is to compare the Average Glandular Dose (AGD) of a photon counting detector (PCD) digital breast tomosynthesis prototype with those of a conventional tomosynthesis system (CTS). Methods: After ethical committee approval, some consenting women older than 40y with highly suspicious breast finding at clinical or imaging evaluation (BIRADS 4c-5) underwent bilateral 2-view tomosynthesis with a CTS and a PCD prototype before breast biopsy. AGD and breast thickness were recorded and compared. To verify the correspondence between displayed and measured dose, a set of measurements was done following the EUREF protocol. Furthermore, entrance surface dose to the contralateral breast was evaluated with 21 thermoluminescent dosimeters placed on a anthropomorphic phantom Alderson RANDO simulating an adult female. Results: 16 women (mean age 70 y; 44–82 y) underwent bilateral 2-view tomosynthesis with both systems. The mean RCC displayed AGD was 0.75 mGy for PC and 1.61 mGy for CS with a 51% mean AGD reduction. The mean RMLO AGD was 0.77 mGy for PC and 1.81 mGy for CS with a 57% mean AGD reduction. The mean LCC AGD was 0.72 mGy for PC and 1.5 mGy for CS with a 50% mean AGD reduction. The mean LMLO AGD was 0.75 mGy for PC and 1.72 mGy for CS with a 55% mean dose reduction. Also considering small compression differences, we found a minimum of 50% dose reduction and a correlation between dose reduction and breast thickness: large breasts seem to benefit more from PCD AGD reduction. The doses delivered to the contralateral breast with the PCD device were up to 85% lower than that delivered with the CTS. The highest differences were relative to the nipple area. Conclusions: Our results demonstrate that PCD tomosynthesis allows a significant dose reduction especially in large breasts and a sensible reduction of dose delivered to the contralateral breast.